Eliminating entry barriers for the provision of banking services: Evidence from ‘banking correspondents’ in Brazil - Assunção, Juliano (Journal of Banking & Finance, 2013)
This paper shows that the contractual arrangement of ‘banking correspondents’ has eliminated entry barriers for the provision of banking services in Brazil. With the bank correspondents, banks are allowed to reach the almost 2200 municipalities without bank branches in 2000, connecting 45 million people to the financial sector. The evidence is based on the estimation of an entry model of financial providers in Brazilian municipalities. I estimate a zero population entry threshold for banking correspondents for the period from 2002 to 2007. The estimated population entry thresholds for bank branches in the same period are relatively stable at approximately 8000–9000 people. The population entry thresholds for the second to fifth players for banking correspondents are also consistently lower than those for bank branches.